Side Effects Following Administration of the First Dose of Oxford-AstraZeneca's Covishield Vaccine in Bangladesh: A Cross-Sectional Study - Nishat Jahan; Fahad Imtiaz Rahman; Poushali Saha; Sadia Afruz Ether; ASM Roknuzzaman; Rapty Sarker; Khondoker Tashya Kalam; Kashfa Haq; Julkar Nyeen; Humayra Zaman Himi; Md. Nazmul Hossain; Mahtab Hossain Chowdhury; et al. (MDPI AG, 2021)
In response to the raging COVID-19 pandemic, Bangladesh started its vaccine administration in early 2021; however, due to the rapid development and launch of the vaccines in the market, many people had concerns regarding the safety of these vaccines. The purpose of this study was to evaluate the side effects that were experienced by the Bangladeshi residents after receiving the first dose of the Oxford-AstraZeneca's Covishield vaccine (ChAdOx1nCoV-19). The study was conducted using both online and printed questionnaires and the data were analysed using SPSS. The results included the responses of 474 vaccine recipients from March-April 2021. Pain at the site of injection, fever, myalgia, fatigue and headache were the most commonly reported symptoms, and the overall side effects were found to be significantly more prevalent in the younger population (p ≤ 0.05). These findings were consistent with the results indicated by the clinical trial of ChAdOx1nCoV-19. Logistic regression analysis further revealed that compared to people aged 70 years or above, the incidence of reported side effects was significantly higher in people aged 18-30 years (odds ratio (OR) = 8.56), 31-40 years, (OR = 5.05), 41-50 years (OR = 4.08), 51-60 years (OR = 3.77) and 61-70 years (OR = 3.67). In addition, a significantly higher percentage of female participants suffered from post-vaccination side effects compared to males (OR = 1.51). It was concluded that the Covishield vaccine was well-tolerated among people of different age groups. Nevertheless, further long-term follow-up study with a larger sample size is warranted to establish the long-term safety of the COVID-19 vaccine.